A meta-analysis of obstetric and neonatal outcomes in patients after treatment of hysteroscopic adhesiolysis - Wenzhi, Xu; Xin, Xu; Ping, Zhou; Hanglin, Wu; Xiaona, Lin (Frontiers in Endocrinology, 2023)
Background: Hysteroscopic adhesiolysis is widely performed in women with intrauterine adhesions. Small observational studies have reported the obstetric and neonatal outcomes, but studies with larger sample sizes are few. Aim: To evaluate the obstetric and neonatal outcomes in women after hysteroscopic adhesiolysis. Methods: We conducted a literature search in July 2022 using the PubMed, Embase, the Cochrane Library, and Web of Science databases, and finally, 32 studies (N = 3812) were included. We did a meta-analysis to estimate the prevalence of placenta-related disorders, including placenta previa, placental abruption, placenta accreta, placenta increta, and retained placenta. We also included other obstetric and neonatal outcomes like postpartum hemorrhage, ectopic pregnancy, oligohydramnios, gestational hypertension, gestational diabetes mellitus, and intrauterine growth restriction. The results were presented as odds ratios (ORs) with 95% confidence intervals (CIs) in studies with a control group, but otherwise as prevalence (%) with 95% confidence intervals (CIs). Results: The overall pregnancy and live birth rates were 58.97% and 45.56%, respectively. The prevalence of placenta previa differed in pregnant women who underwent hysteroscopic adhesiolysis compared with those who did not (OR, 3.27; 95% CI, 1.28-8.36). In studies without a comparative group, the pooled rate of placenta accreta was 7% (95% CI, 4-11) in 20 studies; placenta increta was 1% (95% CI, 0-4) in 5 studies; a retained placenta was 11% (95% CI, 5-24) in 5 studies; postpartum hemorrhage was 12% (95% CI, 8-18) in 12 studies; ectopic pregnancy was 1% (95% CI, 0-2) in 13 studies; oligohydramnios was 3% (95% CI, 1-6) in 3 studies; intrauterine growth restriction was 3% (95% CI, 1-8) in 3 studies; gestational hypertension was 5% (95% CI, 2-11) in 4 studies; and diabetes mellitus was 4% (95% CI, 2-7) in 3 studies. Conclusions: Due to the paucity of good quality comparative data, the question of whether there is an increased prevalence of obstetric and neonatal complications in women after hysteroscopic adhesiolysis compared with the general population remains unanswered. The findings from this review will provide a basis for more well-designed studies in the future.